Report on gender stakeholder co-creation workshops held in Mukono and Masaka districts, Uganda - Omondi, Immaculate A.; Namatovu, Jane; Achandi, Esther; Galiè, Alessandra; Ouma, Emily A. (International Livestock Research Institute, 2024)
In Uganda, given the importance of livestock in the livelihoods of its people and the commitment of public and private actors to transform food systems through sustainable livestock development, SAPLING seeks to improve livelihoods of livestock producers and other actors in the pig, dairy and beef value chains. The Initiative’s gender agenda is to empower women and youth to fully benefit from livestock. By developing interventions that address specific constraints and opportunities that prevent women and youth from benefiting from livestock, the initiative aims to leverage targeting improving livestock productivity to not only enhance livelihoods and nutrition but also empower women farmers and the youth. This would be through targeted interventions that support women and youth’s empowerment and those that counter restrictive gender norms that disadvantage women. To formulate the interventions, a study on gendered empowerment and social and gender norms affecting such empowerment was conducted in Masaka and Mukono districts between 2022 and 2023. A co-creation process that involved stakeholders, drawing on a variety of their perspectives, and informed by empirical evidence, to identify and prioritize aspects of empowerment and gender norms that could be addressed by SAPLING and partners was undertaken. This was through one-day stakeholder and community engagement workshops organized in Masaka and Mukono districts to co-create interventions with stakeholders, with the aim of addressing key gendered constraints and opportunities in the livestock value chains in Uganda. The co-creation process included the following steps: 1. Various speakers presented gender and youth issues in livestock in Uganda; 2. Gender scientists presented results from the study on empowerment and gender norms; 3. Workshop participants discussed the findings; 4. Workshop participants identified possible interventions to address disempowerment and restrictive gender norms; 5. Interventions were prioritized; 6. A plan for action for each intervention was made.